IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. YOGYAKARTA TEKSTIL DI YOGYAKARTA - Sutikno, Annisyatulhuda Rani Ayuningtyas (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2021)
Abstract Corporate Social Responsibility (CSR) is important in addition to the company's goal in seeking profit, it is also in line with the business objectives in Islam, namely benefit. The purpose of this study is to study further how the activities of Corporate Social Responsibility (CSR) at PT. Yogyakarta Textiles and in view of Law no. 40 of 2007 concerning Limited Liability Companies and Maqashid Syari'ah. This research is a type of field research with a qualitative descriptive approach that focuses on the implementation of Corporate Social Responsibility (CSR) at PT. Yogyakarta Textiles. The data used are primary and secondary data collected through interviews and documentation which are then analyzed by data analysis techniques using the theory proposed by Miles and Hubermen with an interactive model. Based on the research analysis, it can be concluded that Corporate Social Responsibility (CSR) at PT. Yogyakarta Textiles in terms of Law no. 40 of 2007 concerning Limited Liability Companies and their implementation in PP No. 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies is still in Article 5 which is not yet appropriate and is reviewed in Maqashid Syari'ah Corporate Social Responsibility (CSR) activities at PT. Yogyakarta Textiles are in accordance with several maintenances such as the maintenance of religion, soul, mind, property and lineage. Keywords: CSR; Maqashid Shari'ah; Limited company   Abstrak Corporate Social Responsibility (CSR) atau tanggung jawab sosial penting disamping tujuan perusahaan dalam mencari keuntungan hal ini juga sejalan kaitannya tujuan usaha dalam Islam yaitu kemaslahatan. Tujuan penelitian ini adalah ingin mengkaji lebih jauh bagaimana kegiatan Corporate Social Responsibility (CSR) di PT. Yogyakarta Tekstil dan dalam pandangan Undang-Undang No. 40 Tahun 2007 Tentang Perseroan Terbatas dan Maqashid Syari'ah. Penelitian ini merupakan jenis penelitian field research (lapangan) dengan pendekatan deskriptif kualitatif yang terfokus pada implementasi Corporate Social Responsibility (CSR) di PT. Yogyakarta Tekstil. Data yang digunakan adalah data primer dan sekunder yang dikumpulkan melalui wawancara dan dokumentasi yang kemudian dianalisis dengan teknik analisis data menggunakan teori yang dikemukakan oleh Miles dan Hubermen dengan model interaktif. Berdasarkan analisis penelitian, dapat disimpulkan Corporate Social Responsibility (CSR) di PT. Yogyakarta Tekstil ditinjau dari Undang-Undang No. 40 Tahun 2007 Tentang Perseroan Terbatas dan pelaksanaannya dalam PP Nomor 47 Tahun 2012 Tentang Tanggung Jawab Sosial Dan Lingkungan Peseroan Terbatas masih ada dalam pasal 5 yang belum sesuai serta ditinjau dalam Maqashid Syari'ah kegiatan Corporate Social Responsibility (CSR) di PT. Yogyakarta Tekstil sudah sesuai dengan beberapa pemeliharaan seperti pemeliharaan agama, jiwa, akal, harta dan keturunan. Kata Kunci: CSR; Maqashid Syari'ah; Perseroan Terbatas.